Coping Strategies Adopted by Migrant Female Head-load Carriers Who Experienced IPV - Baffour, Frank Darkwa (Victims & offenders, 2022)
The physical, sexual and reproductive, and mental health complications posed by Intimate Partner Violence (IPV) raise problems that must be addressed by victims. This study presents qualitative data on the coping strategies employed by 20 head-load carriers (females who carry loads in a saucepan on the head for a fee) who were survivors of IPV. The findings indicate that the head-load carriers adopted strategies such as apologizing or fighting back (interpersonal coping); remaining silent (intrapersonal coping); seeking support from family, friends, or institutions (socio-personal coping); engaging in prayer and hope; and leaving the relationship. Future research and policy implications are also discussed.